Local contect requirements and the manufacture of solar photovoltaic components in South Africa - Kuzwayo, Mandlesizwe (My University, 2018)
The outputs in this report are based on the experiences, beliefs and perceptions of a crosssection of Solar Photovoltaic industry stakeholders on whether Local Content Requirements is an appropriate policy instrument for building a local industry and the extent to which the Local Content Requirements of the Renewable Energy Independent Power Producer Procurement Programme have led to an increase in the South African solar component manufacturing capacity since the programme’s inception in November 2011. Protectionist policies, including Local Content Requirements, were used by now industrialised countries to develop their respective countries, and continue to be used to this day despite World Trade Organisation prohibitions. Four models on building local industries are discussed and their relationship to the two research questions explored. Interview participants agreed that the Renewable Energy Independent Power Producer Procurement Programme was instrumental in building a large-scale local renewable energy industry in the country, created jobs and excitement around manufacturing capacity potential. However, many believe that programme design and implementation interventions are required to improve the programme’s localisation impacts. The latest draft Integrated Resource Plan’s sizeable allocation for Solar Photovoltaic until 2030 presents an opportunity to drastically improve localisation benefits for the country.
Research report submitted to the faculty of Commerce, Law and Management, University of Witwatersrand, in 50% fulfilment of the requirements for the degree of Master of Management in the field of Public and Development Management. March 2018
Keywords: Photovoltaic cells; Photovoltaic power systems--South Africa; Electric power systems